Conformational and structural studies of meso monosubstituted metalloporphyrins—Edge-on molecular interactions of porphyrins in crystals. Issue 1 (7th January 2016) - Senge, Mathias O.; Flanagan, Keith J.; Ryan, Aoife A.; Ryppa, Claudia; Donath, Mandy; Twamley, Brendan
Abstract: A series of meso monosubstituted metalloporphyrins were synthesized to assess the structural chemistry of porphyrins with only one substituent. The structures of four nickel(II) and zinc(II) complexes with either alkyl or aryl residues indicate primarily planar macrocycles. This gives rise to a different type of π-interactions in the crystal and the formation of dimeric, trimeric or tetrameric porphyrin units that function as building blocks for the overall crystal structure. Notably, some structures exhibit a unique edge-on packing of porphyrins, while the molecules of (5- n -butylporphyrinato)nickel(II) forms an unusual bilayer type structure where rows of two porphyrin macrocycles are separated by the alkyl residues arranged in a head-to-head fashion. This adds to the canon of intermolecular porphyrin packing arrangements and is of relevance for the preparation of ordered nanoscopic porphyrin devices. Graphical abstract: